Innovation in the banking industry how can bank X thrive in a digital world? - Portelada, Paulo (2021)
Digital Revolution has been fostering innovation in the banking industry. The rise of FinTechs has broaden the range of options regarding financial services, increasing the expectations of customers who have become more demanding. This thesis shows the application of entrepreneurial methodologies with high customer involvement, in order to provide a concept to a major bank in the Portuguese market, that creates a new revenue stream without reducing its customer base.